2016
DOI: 10.18857/jkpt.2016.28.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bridge Exercise with Abdominal Drawing-in on Balance in Patients with Stroke

Abstract: Purpose: The aim of this study was to evaluate the effect of Bridge exercise with abdominal drawing-in on static and dynamic balance in patients with stroke. Methods: Forty patients with stroke participated in this study. Participation was randomly assigned to the Bridge exercise group (n= 20) and the Bridge exercise with abdominal drawing-in group (n= 20). A bio-feedback device was used when patients performed the Bridge exercise with abdominal drawing-in. This training was performed without any motion on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…20) Another study observed that trunk training facilitated arm and leg movement by improving trunk stability, which in turn led to improved dynamic balance, and this was also consistent with our results. 21) As reported that lumbar stability training reduces excessive lordotic angles in stroke patients and improves weight shift on the affected side as a result of increased trunk and pelvic stability, 22) we observed that our intervention improved weight shift in the affected side and thus lengthened the stance phase in the affected side during walking, which led to increased swing phase in the unaffected side, thereby increasing stride length. 23) In essence, lumbar stability training improved lumbar alignment, erector spinae and hamstring activities, gait speed, and stride length in stroke patients, and these results suggest that lumbar stabilization training through lumbar lordosis control may also be effective as the conventional physical therapy in improving postural stability and ambulation in stroke patients.…”
Section: β…³ Discussionsupporting
confidence: 60%
“…20) Another study observed that trunk training facilitated arm and leg movement by improving trunk stability, which in turn led to improved dynamic balance, and this was also consistent with our results. 21) As reported that lumbar stability training reduces excessive lordotic angles in stroke patients and improves weight shift on the affected side as a result of increased trunk and pelvic stability, 22) we observed that our intervention improved weight shift in the affected side and thus lengthened the stance phase in the affected side during walking, which led to increased swing phase in the unaffected side, thereby increasing stride length. 23) In essence, lumbar stability training improved lumbar alignment, erector spinae and hamstring activities, gait speed, and stride length in stroke patients, and these results suggest that lumbar stabilization training through lumbar lordosis control may also be effective as the conventional physical therapy in improving postural stability and ambulation in stroke patients.…”
Section: β…³ Discussionsupporting
confidence: 60%
“…The bridge exercise with ADIM was more efficient for increasing balance ability in patients with stroke. 2 Abdominal muscle activity, in combination with the ADIM, affected the grip strength, positively. 3 Monica et al 14 suggested that a lateral TrA slide in patients with chronic lower back pain is an effective means of pain reduction.…”
Section: Introductionmentioning
confidence: 97%